2020
DOI: 10.1002/art.41182
|View full text |Cite
|
Sign up to set email alerts
|

Role of Chondrocytes in the Development of Rheumatoid Arthritis Via Transmembrane Protein 147–MediatedNF‐κB Activation

Abstract: Objective. We have previously reported that the coactivation of NF-κB and STAT3 in nonimmune cells, including synovial fibroblasts, enhances the expression of NF-κB target genes and plays a role in chronic inflammation and rheumatoid arthritis (RA). This study was undertaken to examine the role of NF-κB activation in chondrocytes and better understand the pathogenesis of RA. Furthermore, transmembrane protein 147 (TMEM147) was investigated as a representative NF-κB activator in chondrocytes.Methods. Clinical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 47 publications
1
32
0
Order By: Relevance
“…Indeed, activation tends to occur more easily in tissue-specific non-immune cells such as tracheal basement cells, synovial fibroblasts, keratinocytes, kidney tubule cells, and chondrocytes. Therefore, through the IL-6 amplifier, these cells could regulate several tissue specific-inflammatory diseases [56][57][58][59][60]. Furthermore, activation of the IL-6 amplifier depends on various environmental and genetic factors.…”
Section: Il-6-stat3 Signaling As a Potential Cause Of The Ards Via Cymentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, activation tends to occur more easily in tissue-specific non-immune cells such as tracheal basement cells, synovial fibroblasts, keratinocytes, kidney tubule cells, and chondrocytes. Therefore, through the IL-6 amplifier, these cells could regulate several tissue specific-inflammatory diseases [56][57][58][59][60]. Furthermore, activation of the IL-6 amplifier depends on various environmental and genetic factors.…”
Section: Il-6-stat3 Signaling As a Potential Cause Of The Ards Via Cymentioning
confidence: 99%
“…The IL-6 amplifier is a hyper NF-κB activation machinery in non-immune cells induced by the simultaneous activation of NF-κB and STAT3. It induces a massive and sustained production of NF-κB target genes, including IL-6, chemokines, and growth factors, which is critical for the development of various disease models including lung transplantation, rheumatoid arthritis, and multiple sclerosis [ 56 60 ]. Furthermore, we have shown that the co-activation of NF-κB and STAT3, which is evidence of activation of the amplifier, is observed in clinical specimens from patients with inflammatory diseases [ 56 , 61 ].…”
Section: Il-6-stat3 Signaling As a Potential Cause Of The Ards Via Cymentioning
confidence: 99%
“…An important point to note is that cartilage participates in both inflammatory and bone destruction phases (34). Chondrocytes are only resident cells in the cartilage, which not only act as target cells of inflammatory mediators, but also serve as effector cells and play an important role in cytokine cascades (15,(35)(36)(37)(38). Insights into the cascades between chondrocytes and cartilagereactive T cells could be helpful to find new biological markers and therapeutic targets of inflammatory arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike a number of other cytokines, IL-6 can activate cells through both membrane-bound (IL-6R) and soluble receptors (sIL-6R), thus widening the number of cell types responsive to this cytokine (48)(49)(50)(51). IL-6-mediated inflammation amplifier was reported as a key molecular mechanism in chronic inflammation (15,52,53), which triggers a vicious circle of escalating RA disease activity (51,54,55). IL-6 plus TNF-a or IL-6 plus IL-17 can trigger IL-6 amplifier, leading to positive feedback for IL-6 signaling (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation